Design and development of an interactive digital spectral library - Adam, Siti Nooradzah (2012)
Spectral library is a database system that stores the spectral data of materials. The materials include vegetations, soils, minerals, rocks, water and manmade. Many spectral libraries were already available online and being referred by end users. However, these libraries of materials were specifically designed for their own use. Therefore, there is a need to develop a practical spectral library towards facilitating spectral remote sensing technological development in Malaysia. This library will be made available in public domain as these data are useful as reference material for future study. Spectral data from laboratory or field measurements, need to be stored and managed in a specially designed database that act as a unified repository of spectral signatures as well as additional information (metadata or ancillary data) which describes the relationship to specific physiographic and ecological background conditions of the areas under observation. The process of designing and developing the library involves selecting documents for inclusion, suitable metadata set, assigning metadata to each document or group of documents, designing the form for the collection in terms of document formats, searchable indexes, browsing facilities, building the necessary indexes and data structures and putting the collection in place for others to use. Furthermore, it will be developed in such a way so that registered users can contribute to the richness of the data in the library. The developed spectral library is online or web based, so it provides the convenient share of spectral information not only in Malaysia but throughout the world. The spectral library also acts as a center for spectral identification and cataloguing as well as providing useful information for any remote sensing based research in Malaysia.